2013
DOI: 10.1080/17408989.2013.837435
|View full text |Cite
|
Sign up to set email alerts
|

The Open Society and coach education: a philosophical agenda for policy reform and future sociological research

Abstract: Background: The realisation of the strategic importance of high quality coaching

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…For example, when the participants in the present study received different perspectives and/or personalized questions from other group members (and on occasion the tutors) about their explanations, they had to justify their positions, which may have helped them to move beyond mere information exchange (Gray, 2005) and identify differences in understandings, as well as weaknesses in their initial explanations (Choi, Land, & Turgeon, 2005). This was especially apparent when two or more participants holding opposing views would engage in critical discussion (Piggott, 2013). Goos, Galbraith, and Renshaw (2002) Of course, the mixed nature must be acknowledged, since the levels of experience and qualification of coaches within the group varied from 0-6 years and L1 to L3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, when the participants in the present study received different perspectives and/or personalized questions from other group members (and on occasion the tutors) about their explanations, they had to justify their positions, which may have helped them to move beyond mere information exchange (Gray, 2005) and identify differences in understandings, as well as weaknesses in their initial explanations (Choi, Land, & Turgeon, 2005). This was especially apparent when two or more participants holding opposing views would engage in critical discussion (Piggott, 2013). Goos, Galbraith, and Renshaw (2002) Of course, the mixed nature must be acknowledged, since the levels of experience and qualification of coaches within the group varied from 0-6 years and L1 to L3.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, participants at least seemed to be more aware of the social norms and assumptions that might drive their behaviour (Abraham & Collins, 2011), and, it could be argued, were therefore less likely to engage in the mere transmission of dogma, a potential danger of knowledge sharing in CoPs (Piggott, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, we believe enough promise exists 608 recent four-year coach tracking study found that the cost, timing, and travel involved in 613 accessing coach education are major barriers to uptake (Sports Coach UK, 2012b), it seems 614 Web 2.0 platforms such as blogs could allow coach educators to provide ongoing support to 615 those coaches undertaking certification courses at relatively little monetary and "time" 616 expense to both parties when compared to face-to-face solutions (Piggott, 2013). 617…”
Section: Conclusion 605mentioning
confidence: 99%